Radiation-induced acute injury of intensity-modulated radiotherapy versus three-dimensional conformal radiotherapy in induction chemotherapy followed by concurrent chemoradiotherapy for locoregionally advanced nasopharyngeal carcinoma: a prospective cohort study - Zexin Yao (Nature Portfolio, 2021)
Abstract To address whether the addition of intensity-modulated radiotherapy (IMRT) compared to three-dimensional conformal radiotherapy (3D-CRT) aggravate radiation-induced acute injury of locoregionally advanced nasopharyngeal carcinoma (LANPC) patients with induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT). We conducted a prospective study of 182 patients in the stage III to IVb with biopsy-proven nonmetastatic LANPC who newly underwent radiotherapy and sequentially received IC, followed by CCRT at our institution. Occurring time of radiation-induced toxicities were estimated and compared using the Kaplan–Meier method and Log-rank test. The most severe acute toxicities included oral mucositis in 97.25% and dermatitis in 90.11%. Subset analysis revealed that Grade 3–4 acute dermatitis were significantly higher in the IMRT than 3D-CRT. Oral mucositis and dermatitis were the earliest occurrence of acute injuries (2 years: 60.44% and 17.58%). Patients in IMRT group achieved significantly lower risk of bone marrow toxicity, but higher risk of leukopenia and gastrointestinal injury. Multivariate analyses also demonstrated that IMRT, female gender and hepatitis were the independent prognostic factors for bone marrow toxicity. In a combined regimen of IC followed by CCRT for the treatment of LANPC, IMRT seems to be an aggressive technique with a trend towards increased gastrointestinal and hematological toxicities, but decreased bone marrow toxicity than those treated with 3D-CRT. This study provides a comprehensive summary of prospective evidence reporting the side effects in the management of LANPC patients. We quantify the occurrence risks of chemoradiotherapy-induced acute injuries through analysis of time-to-event.